THE IMMUTABILITY OF THE CLASSICAL GEOPOLITICS. AN APPROACH TO THE RELATIONS BETWEEN RUSSIA AND THE UNITED STATES OF AMERICA - Cutrona, Sebastián Antonino (2013)
Within the frame of postmodernism, the main theoretical bases of the traditional Geopolitics started to be strongly questioned by a new current group of researchers identified with the Critical School of this discipline. However, the different shades in the relations between Russia and the United States of America seem to revalidate the basic premises of the traditional Geopolitics: Halford Mackinder’s Heartland, George Kennan’s Contention and The Spheres of Influence.